Etika Perempuan Muslimah di Ruang Publik: Tinjauan Hadis dalam Konteks Modelling - Meidina, Najwa; Zakiyah, Ulfah; Abil Ash (IAIN KENDARI, 2026)
This study aims to analyze the construction of Muslim women's ethics in the digital public sphere through a thematic hadith approach to contemporary modeling practices. This research employs a library research method with a qualitative approach, utilizing thematic (mawḍū‘ī) hadith analysis combined with a normative-contextual framework. Data sources include classical and contemporary hadith literature, scholarly works, and studies on gender and media. The findings indicate that hadith does not prohibit women from participating in the public sphere; rather, it constructs an ethical framework that includes covering the awrah substantively, avoiding tabarruj, maintaining the value of ḥayā’, and observing ethical interaction and social considerations. In the context of digital modeling, the main issue lies not in the profession itself, but in the form of visual representation it produces. Modeling is acceptable as long as it does not lead to objectification or bodily exploitation. This study highlights the importance of contextualizing hadith in response to the transformation of the public sphere into digital spaces and contributes to the development of hadith studies within contemporary visual culture discourse.